Motogp Mandalika 2025 As Indonesia’s Soft Power Strategy to Uphold Its Safety Image Amid Political Unrest - Erick Herlangga; Joseph Aldo Irawan (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
In late August 2025, Indonesia was rocked by nationwide political demonstrations, triggered by the death of a delivery driver at the hands of police. These protests turned violent, leading to multiple casualties, injuries, and arson attacks on government and commercial buildings. This unrest has raised international concerns regarding the country’s safety image. This paper uses a qualitative descriptive approach to analyze secondary sources, such as news media, government releases, and academic literature, to explore how hosting the 2025 MotoGP at the Mandalika Circuit could be used as a nation-branding strategy to counter negative perceptions. The study draws on nation branding theory, destination image concepts, event leveraging, and Situational Crisis Communication Theory (SCCT). Findings suggest that Indonesian authorities are actively promoting MotoGP Mandalika 2025 as an opportunity to demonstrate the country’s resilience and safety standards. We analyze two scenarios: one in which the event is canceled and one where it is successfully executed. The paper argues that canceling the event, unless due to a legitimate health crisis, would signal weakness and harm the country's image, while proceeding with it would reflect confidence and effective crisis management. As a "brand shield," the MotoGP event is being leveraged to reinforce the narrative of Indonesia as a stable and safe international sports host, demonstrating the country's ability to manage crises while showcasing its commitment to safety and resilience.